Respuesta :
Q1. The answer is 1.32 s.
The kinetic equation used to calculate the time is:
d = v1 t + 1/2 at²
d - distance
v1 - initial velocity
t - time
a - gravitational acceleration
We know:
d = - 8.52 m (negative because it is downwards)
v1 = 0 (there is no initial velocity in free fall)
a = - 9.8 m/s² (negative in free falls)
d = v1 t + 1/2 at²
- 8.52 = 0 * t + 1/2 * - 9.8 * t²
- 8.52 = 0 - 4.9 t²
-8.52 = -4.9 t²
t² = -8.52/-4.9
t² = 1.74
t = √1.74
t = 1.32 s
Q2. PART A) The answer is 35 m.
The kinetic equation that can be used is:
v2² = v1² +2ad
d - distance
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
We know:
v2 = 0 (The final velocity is at the peak so it is 0)
v1 = 26.2 m/s
a = 9.8 m/s² (negative in free falls)
d = ?v2² = v1² +2ad
0 = 26.2² + 2 * ( - 9.8) * d
0 = 686.44 - 19.6d
19.6d = 686.44
d = 686.44/19.6
d = 35.0 m
Q2. PART B) The answer is 26.2 m/s.
The velocity at what is the vase moving when Rex catches is v2.
The kinetic equation that can be used is:
v2² = v1² + 2*a*d
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
d - distance
We know:
v2 = ?
v1 = 0 (in free fall)
a = - 9.8 m/s² (negative in free falls)
d = - 35 m (negative because it is downwards)v2² = v1² + 2*a*d
v2² = 0 + 2 * -9.8 * -35
v2² = 686
v2 = √686
v2 = 26.2 m/s
Q3. PART A) The answer is -147 m/s
The kinetic equation that can be used is:
v2 = v1 + a * t
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
t - time
We know:
v1 = 0 (the initial speed is 0 at free fall)
v2 = ?
a = - 9.8 m/s² (negative in free fall)
t = 15s
v2 = v1 + a * t
v2 = 0 + -9.8 * 15
v2 = -147 m/s
Q3. PART B) The answer is 1102.5 m.
The kinetic equation that can be used is:
v2² = v1² +2ad
d - displacement
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
We know:
v2 = -147 m/s
v1 = 0 (in free fall)
a = -9.8 m/s² (negative in free falls)
v2² = v1² +2ad
-147² = 0 + 2 * -9.8 * d
21609 = -19.6d
d = 21609 / -19.6
d = - 1102.5 m
Displacement is negative, but the height cannot be negative so it is 1102.5m
Q4. PART A) The answer is -13.3 m/s
The kinetic equation that can be used is:
v2 = v1 + a * t
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
t - time
We know:
v2 = ?
v1 = 21 m/s
a = 9.8 m/s (negative in free fall)
t = 3.5s
v2 = v1 + a * t
v2 = 21 + (-9.8)*3.5
v2 = 21 - 34.3
v2 = -13.3 m/s
Q4. PART B) The answer is 9.025 m
The kinetic equation that can be used is:
v2² = v1² +2ad
d - displacement
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
We know:
v2 = -13.3 m/s
v1 = 0 (in free fall)
a = -9.8 m/s (in free fall)
v2² = v1² +2ad
-13.3² = 0 + 2 * -9.8 * d
176.89 = 0 - 19.6 * d
176.89 = -19.6 * d
d = 176.89 / -19.6
d = - 9.025 m
Displacement is negative, but the height cannot be negative so it is 9.025 m
Q4. PART C) The answer is the orange is travelling down.
According to the part B of the question, displacement is negative value. The negative value of the displacement is when object goes downwards, thus, it travels down.
Q5. PART A) The answer is 24.7 m
v2² = v1² +2ad
d - displacement
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
We know:
v2 = 0 (when it reaches the ground)
v1 = 22 m/s
t = 6.4 s
a = -9.8 m/s (in free fall)
v2² = v1² +2ad
0 = 22² + 2 * -9.8 * d
0 = 484 + -19.6d
-484 = - 19.6d
d = -484/-19.6
d = 24.7 m
PART B) The answer is 2.24m
The kinetic equation used to calculate the time is:
v2 = v1 + a*h
h - height
v1 - initial velocity
v2 - final velocity
a - gravitational acceleration
We know:
v1 = 22 m/s
v2 = 0
h = ?
a = -9.8 m/s (negative in free fall)
v2 = v1 + a*h
0 = 22 + -9.8 * h
-22 = -9.8h
h = -22/-9.8
h = 2.24 m